Book of duas for children - Gillani-Williams, Fawzia (KUTAB KHANA New Dehli, 2005)
"Duas for Children" is a beautifully illustrated collection that introduces young readers to essential prayers and supplications in Islam. It aims to instill a sense of spirituality and connection to God, making learning about faith engaging and accessible for kids.